Acrylate OCA optical adhesive for folding screen and production process thereof

By using rosin composite resin crosslinking agent and inorganic modified additives in OCA optical glue for crosslinking polymerization and curing, the problem of insufficient peel strength and high temperature resistance of traditional OCA optical glue is solved, and its peel strength and resistance are significantly improved. High temperature performance ensures the stability and durability of the product.

CN118006264BActive Publication Date: 2025-02-14JIANGXI HAOZE OPTICAL FILM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311774963.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-02-14
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

Traditional acrylate OCA optical glue has low peel strength during the folding screen manufacturing process and is insufficient in high temperature resistance, which is prone to peeling, falling off or deformation, affecting the stability and durability of the product.

Method used

Under nitrogen protection, butyl methacrylate, acrylic acid, glycidyl acrylate, initiator and rosin composite resin crosslinking agent are added to the reactor for crosslinking polymerization, and an adhesive with high crosslinking density is prepared. Inorganic modified additives are added for curing to form an acrylate OCA optical glue with high peel strength and high temperature resistance.

Benefits of technology

It significantly improves the peel strength and high temperature resistance of OCA optical glue, avoids peeling or falling off during use, and ensures the stability and durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118006264B_ABST
    Figure CN118006264B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical adhesives, and discloses an acrylate OCA optical adhesive for folding screens and a production process thereof. The optical adhesive comprises the following raw materials: butyl methacrylate, acrylic acid, glycidyl acrylate, dicumyl peroxide, a rosin composite resin crosslinking agent, and an inorganic modified additive. The rosin composite resin crosslinking agent is crosslinked and polymerized with a matrix raw material to make the prepared acrylate OCA optical adhesive have a higher crosslinking density, a tighter interface bonding, and improved peel strength of the OCA optical adhesive. Meanwhile, the rosin composite resin crosslinking agent can further improve the peel strength of the acrylate OCA optical adhesive, and the inorganic modified additive can improve the high temperature resistance of the acrylate OCA optical adhesive. The comprehensive play of these effects broadens the application scope of the acrylate OCA optical adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical adhesives, and in particular to an acrylic ester (OCA) optical adhesive for folding screens and a production process thereof. Background Art

[0002] In recent years, with the continuous advancement of mobile phone upgrades, in order to make it convenient to carry, foldable mobile phones have gradually entered the market and are popular with consumers, and the requirements for folding screens are getting higher and higher. OCA optical adhesive is a substrate-free optical double-sided tape with excellent properties such as high light transmittance, water resistance, UV resistance, and aging resistance. However, the peel strength of traditional OCA optical adhesive is low. In the manufacturing process of folding screens, OCA optical adhesive is used to bond various optical components. These components need to withstand various external forces during use, such as touch, press, etc. If the peel strength of OCA optical adhesive is insufficient, it is easy to peel or fall off. Therefore, OCA optical adhesive needs to have a high peel strength to avoid peeling or falling off during use, affecting the stability and durability of the product. In addition, the high temperature resistance of traditional OCA optical adhesive is poor, because the folding screen needs to undergo high temperature treatment processes such as hot pressing during the manufacturing process. If the high temperature resistance of OCA optical adhesive is poor, deformation, cracking and other problems will occur. In order to avoid high temperature loss of OCA optical adhesive, it is also necessary to have good high temperature resistance to ensure its stability and reliability.

[0003] The invention patent with application number CN202210250273.6 discloses a method for preparing a flexible, highly waterproof and high temperature resistant OCA optical adhesive and an OCA optical adhesive film. The OCA optical adhesive is obtained by first synthesizing a polyurethane acrylate prepolymer and a double-bond terminated polydimethylsiloxane prepolymer, and then blending with a heat-resistant functional acrylate monomer mixture to obtain an OCA optical adhesive, which has high waterproofness, flexibility and high temperature resistance. The invention patent with application number CN107353854B discloses an OCA optical adhesive and an OCA optical adhesive film. By adding a saturated polyacrylate with a crosslinkable group to the matrix raw material, the components of the optical adhesive are optimized and selected to obtain an OCA optical adhesive film with high viscosity and good peelability. However, there is no improvement in the high temperature resistance of the OCA optical adhesive, which actually has certain limitations on the application of OCA optical adhesive in the field of folding screens. Therefore, it is of great significance to develop an acrylate OCA optical adhesive with high peel strength and excellent high temperature resistance. Summary of the invention

[0004] The purpose of the present invention is to provide an acrylic ester OCA optical adhesive for folding screens and a production process thereof, which solves the following technical problems:

[0005] (1) Solved the problem of poor peel strength of acrylic OCA optical adhesive;

[0006] (2) Solved the problem of poor high temperature resistance of acrylic OCA optical adhesive;

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A production process of acrylic ester OCA optical adhesive for folding screens, comprising the following steps:

[0009] (1) In parts by weight, under the protection of nitrogen, add 30 to 70 parts of butyl methacrylate, 3 to 5 parts of acrylic acid, 20 to 50 parts of glycidyl acrylate, 0.6 to 5 parts of initiator and 0.4 to 1 part of rosin composite resin crosslinking agent into a reactor, raise the temperature to 50 to 70° C., stir for 1 to 2 hours, then add 2 to 4 parts of inorganic modified additives, continue stirring for 1 to 3 hours, and obtain an adhesive;

[0010] (2) The adhesive is placed in a vacuum drying oven at a temperature of 60 to 70° C. for curing for 5 to 10 minutes to form a rubber compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0011] Furthermore, in step (1), the initiator is any one of dicumyl peroxide and benzoyl peroxide.

[0012] Through the above technical scheme, dicumyl peroxide is used as an initiator to initiate cross-linking polymerization of butyl methacrylate, acrylic acid, glycidyl acrylate and rosin composite resin cross-linking agent to prepare an adhesive with a high cross-linking density, which is then coated and cured to obtain acrylate OCA optical adhesive.

[0013] Furthermore, the production process of the rosin composite resin cross-linking agent comprises the following steps:

[0014] S1: under the protection of nitrogen, epoxy compound, chloroacetic acid resin and rosin resin are added to toluene, and then a catalyst is added, and refluxed and stirred for 2 to 4 hours. After the reaction is completed, the product is filtered, and then washed and dried to obtain a modified rosin composite resin;

[0015] S2: Add the modified rosin composite resin and acryloyl chloride into toluene, stir until completely dissolved, then add pyridine, mix evenly, and react at 30-40°C for 4-10 hours. After the reaction is completed, perform reduced pressure distillation and vacuum drying on the product to obtain a rosin composite resin crosslinking agent.

[0016] Furthermore, in step S1, the epoxy compound is any one of ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether.

[0017] Furthermore, in step S1, the catalyst is any one of tetrabutylammonium bromide and tetramethylammonium bromide.

[0018] Through the above technical scheme, under the catalytic action of the catalyst, the carboxyl groups in the chlorovinyl resin and rosin resin structures can undergo a ring-opening reaction with the epoxy groups in the epoxy compound, thereby grafting the rosin resin into the chlorovinyl resin structure to obtain a modified rosin composite resin, and then the hydroxyl groups generated by the ring-opening reaction react with the acyl chloride groups in the acryloyl chloride structure under the action of pyridine, so that the acryloyl chloride is grafted into the structure of the modified rosin composite resin to obtain a rosin composite resin crosslinking agent.

[0019] Furthermore, the production process of the inorganic modified additive comprises the following steps:

[0020] Ⅰ: Add 2,3-epoxypropyltrimethylammonium chloride, talc and deionized water into the reactor, stir to mix them evenly, then start to drop sodium hydroxide solution, adjust the pH value of the system to keep it between 9.5 and 10, place it at 70 to 90° C. for aging for 5 to 10 hours after the dropwise addition, then centrifuge and wash to obtain intercalated modified talc;

[0021] Ⅱ: Mix the polyetheramine and isopropanol, increase the temperature to 60-80°C, stir evenly, then add the intercalated modified talc, react for 10-20 hours, and after the reaction is completed, cool the product to room temperature, then filter and separate the solid sample, wash and vacuum dry it to obtain an inorganic modified additive.

[0022] Furthermore, in step I, the particle size of the talcum powder is 15 to 25 μm.

[0023] Furthermore, in step II, the mass ratio of the intercalated modified talc powder to the polyetheramine is 1:1-2.

[0024] Furthermore, in step II, the number average molecular weight of the polyetheramine is 1000.

[0025] Through the above technical scheme, 2,3-epoxypropyltrimethylammonium chloride is introduced into the interlayer of talc powder by an in-situ intercalation method to obtain intercalation modified talc powder, and then under the action of high temperature, the epoxy groups in the intercalation modified talc powder can undergo a ring-opening reaction with the amino groups at both ends of the polyetheramine molecular chain, and then the polyetheramine is grafted into the intercalation modified talc powder to obtain an inorganic modified additive.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention uses a rosin composite resin crosslinking agent to crosslink and polymerize with butyl methacrylate, acrylic acid, and glycidyl acrylate monomers to form an adhesive A with a high degree of crosslinking, so that the interface bonding is tighter, its cohesive force is enhanced, and the peel strength of the OCA optical adhesive is improved; on the other hand, the chloroacetic acid resin has good flexibility, which can ensure that the acrylate OCA optical adhesive is not easy to break when subjected to external force, thereby ensuring the quality and stability of the product. At the same time, the rosin resin can improve the wettability between the OCA optical adhesive and the adherend, and its ternary phenanthrene ring structure can also enhance its cohesive force and adhesion. The rosin resin is grafted into the chloroacetic acid resin structure, which can improve the peel strength of the OCA optical adhesive and avoid peeling or falling off during use, which affects the stability and durability of the product.

[0028] (2) The present invention prepares an inorganic modified additive. On the one hand, the inorganic modified additive contains polyetheramine, which can participate in the curing process of acrylate OCA optical adhesive, so that the talc powder and the acrylate OCA optical adhesive have good bonding force, and then give full play to the advantages of rigid particles, produce a skeleton support effect, and improve the high temperature resistance of the acrylate OCA optical adhesive; on the other hand, the polyetheramine contains a large number of ether bonds, which can improve the bonding strength of the acrylate OCA optical adhesive, and at the same time make the talc powder evenly distributed in the matrix to avoid agglomeration. The talc powder has a lamellar structure, which can produce a barrier effect, reduce the escape of thermal degradation products of the acrylate OCA optical adhesive, and then improve the high temperature resistance of the acrylate OCA optical adhesive. The combined effect of these effects broadens the application range of the acrylate OCA optical adhesive.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is an infrared spectrum test chart of the rosin composite resin crosslinking agent prepared in Example 1 of the present invention.

[0032] Figure 2 The scanning electron microscope images are of the talcum powder of the present invention and the inorganic modified additive prepared in Example 1. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] 1. Preparation of rosin composite resin crosslinking agent

[0036] S1: Under the protection of nitrogen, 1.8 g of 1,4-butanediol diglycidyl ether, 5.4 g of chloroacetic acid resin and 2.4 g of rosin resin were added to toluene, and then 0.2 g of tetrabutylammonium bromide was added, and refluxed and stirred for 3 h. After the reaction was completed, the product was filtered, and then washed and dried to obtain a modified rosin composite resin;

[0037] S2: Add 3.6 g of modified rosin composite resin and 1.4 g of acryloyl chloride to toluene, stir until completely dissolved, then add 0.15 g of pyridine, mix evenly, and react at 36°C for 6 h. After the reaction, distill the product under reduced pressure and vacuum dry it to obtain a rosin composite resin crosslinker.

[0038] The infrared test of chlorovinyl resin, modified rosin composite resin and rosin composite resin crosslinking agent was carried out by using Vertex 70v Fourier infrared spectrometer of Bruker Company, USA. Figure 1 As shown, the sample was prepared by potassium bromide tablet method, and the spectral scanning range was 4000cm -1 ~500cm -1 , analysis shows that in the infrared spectrum of chloroacetic acid resin, 1724cm -1 The stretching vibration peak of C=O in the carboxyl group is 3328 cm -1 The stretching vibration peak of OH in the carboxyl group is 698 cm -1 The peak at 3386cm is the stretching vibration peak of C-Cl. -1 The peak at 1158cm is the stretching vibration peak of the hydroxyl group. The absorption peak intensity of the hydroxyl group becomes stronger. -1 The stretching vibration peak of ether bond COC is 1764cm in the infrared spectrum of rosin composite resin crosslinker. -1 The stretching vibration peak of the ester group C=O is 3036cm -1The stretching vibration peak of the alkenyl group CH is at the top, while the stretching vibration peak of the hydroxyl group disappears. This is because the hydroxyl group produced by the ring-opening reaction undergoes a substitution reaction with the halogen group in the allyl chloroformate structure, grafting acryloyl chloride into the structure of the modified rosin composite resin, which indicates that the grafting is successful.

[0039] 2. Preparation of Inorganic Modified Additives

[0040] Ⅰ: Add 8.6g of 2,3-epoxypropyltrimethylammonium chloride, 5.3g of talc and deionized water into the reactor, stir to mix evenly, then start to drop a 20% sodium hydroxide solution, adjust the pH value of the system to 9.8, place it at 80°C for aging for 8h after the dropwise addition, then centrifuge and wash to obtain intercalated modified talc;

[0041] Ⅱ: Mix 3.4g of polyetheramine and isopropanol, raise the temperature to 70°C, stir evenly, add 2.5g of intercalated modified talc, react for 15h, and after the reaction is completed, cool the product to room temperature, filter and separate the solid sample, wash and vacuum dry it to obtain an inorganic modified additive.

[0042] The morphology of talcum powder and inorganic modified additives was analyzed. The test results are shown in Figure 2 , where A is talcum powder, B is inorganic modified additive, Figure 2 It can be seen that the surface of the original talcum powder is smooth, while the surface of the inorganic modified additive is rough. This is because 2,3-epoxypropyltrimethylammonium chloride is introduced into the interlayer of talcum powder by the in-situ intercalation method, and then the epoxy group can undergo a ring-opening reaction with the amino groups at both ends of the polyetheramine molecular chain, so that the high molecular weight polyetheramine is distributed on the surface of talcum powder, resulting in the roughness of the talcum powder surface.

[0043] 3. Preparation of acrylate OCA optical adhesive

[0044] (1) In parts by weight, under the protection of nitrogen, 30 parts of butyl methacrylate, 3 parts of acrylic acid, 20 parts of glycidyl acrylate, 0.6 parts of dicumyl peroxide and 0.4 parts of rosin composite resin crosslinking agent were added to a reactor, the temperature was raised to 50°C, stirred for 1 hour, and then 2 parts of inorganic modified additives were added, and stirring was continued for 1 hour to obtain an adhesive;

[0045] (2) The adhesive is placed in a vacuum drying oven at a temperature of 60° C. for curing for 5 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0046] Example 2

[0047] Preparation of acrylate OCA optical adhesive

[0048] (1) In parts by weight, under the protection of nitrogen, 50 parts of butyl methacrylate, 4 parts of acrylic acid, 35 parts of glycidyl acrylate, 2.5 parts of dicumyl peroxide and 0.8 parts of rosin composite resin crosslinking agent were added to a reactor, the temperature was raised to 60°C, stirred for 1.5 hours, and then 3 parts of inorganic modified additives were added, and stirring was continued for 2 hours to obtain an adhesive;

[0049] (2) The adhesive is placed in a vacuum drying oven at a temperature of 65°C for curing for 8 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0050] The preparation methods of the rosin composite resin crosslinking agent and the inorganic modified additive are the same as those in Example 1.

[0051] Example 3

[0052] Preparation of acrylate OCA optical adhesive

[0053] (1) In parts by weight, under the protection of nitrogen, 70 parts of butyl methacrylate, 5 parts of acrylic acid, 50 parts of glycidyl acrylate, 5 parts of diisopropylbenzene peroxide and 1 part of rosin composite resin crosslinking agent were added to a reactor, the temperature was raised to 70°C, stirred for 2 hours, and then 4 parts of inorganic modified additives were added, and stirring was continued for 3 hours to obtain an adhesive;

[0054] (2) The adhesive is placed in a vacuum drying oven at a temperature of 70°C for curing for 10 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0055] The preparation methods of the rosin composite resin crosslinking agent and the inorganic modified additive are the same as those in Example 1.

[0056] Comparative Example 1

[0057] Preparation of acrylate OCA optical adhesive

[0058] (1) In parts by weight, under the protection of nitrogen, 50 parts of butyl methacrylate, 4 parts of acrylic acid, 35 parts of glycidyl acrylate, 2.5 parts of dicumyl peroxide and 0.8 parts of rosin composite resin crosslinking agent were added to a reactor, the temperature was raised to 60° C., and stirred for 1.5 hours to obtain an adhesive;

[0059] (2) The adhesive is placed in a vacuum drying oven at a temperature of 65°C for curing for 8 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0060] The preparation method of the rosin composite resin crosslinking agent is the same as that in Example 1.

[0061] Comparative Example 2

[0062] Preparation of acrylate OCA optical adhesive

[0063] (1) In parts by weight, under the protection of nitrogen, 50 parts of butyl methacrylate, 4 parts of acrylic acid, 35 parts of glycidyl acrylate, and 2.5 parts of dicumyl peroxide were added to a reactor, the temperature was raised to 60°C, and the mixture was stirred for 1.5 hours. Then, 3 parts of an inorganic modified additive was added, and the mixture was stirred for 2 hours to obtain an adhesive;

[0064] (2) The adhesive is placed in a vacuum drying oven at a temperature of 65°C for curing for 8 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0065] The preparation method of the inorganic modified additive is the same as that in Example 1.

[0066] Comparative Example 3

[0067] Preparation of acrylate OCA optical adhesive

[0068] (1) In parts by weight, under the protection of nitrogen, 50 parts of butyl methacrylate, 4 parts of acrylic acid, 35 parts of glycidyl acrylate, 2.5 parts of dicumyl peroxide and 0.8 parts of rosin composite resin crosslinking agent were added to a reactor, the temperature was raised to 60°C, stirred for 1.5 hours, and then 0.2 parts of talc and 0.1 parts of polyetheramine were added, and stirring was continued for 2 hours to obtain an adhesive;

[0069] (2) The adhesive is placed in a vacuum drying oven at a temperature of 65°C for curing for 8 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0070] The preparation method of the rosin composite resin crosslinking agent is the same as that in Example 1.

[0071] Comparative Example 4

[0072] (1) Under the protection of nitrogen, 50 parts by weight of butyl methacrylate, 4 parts of acrylic acid, 35 parts of glycidyl acrylate, and 2.5 parts of dicumyl peroxide were added to a reactor, the temperature was raised to 60° C., and stirred for 1.5 hours to obtain an adhesive;

[0073] (2) The adhesive is placed in a vacuum drying oven at a temperature of 65°C for curing for 8 minutes to form a glue compound, which is then pressed into a sheet-like film, cooled, and then packaged with a release film to obtain an acrylate OCA optical adhesive.

[0074] Performance Testing

[0075] The acrylate OCA optical adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were cut into 10 cm × 5 cm specifications and pasted on standard steel plates to make samples. According to GB / T 2792-2014 "Test method for peel strength of adhesive tapes", the samples and the samples treated in a constant temperature box at 100°C for 48 hours were subjected to 180° peel strength tests to evaluate their peel strength and high temperature resistance. The release films of the acrylate OCA optical adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 4 of the present invention were removed and pasted on the surface of a polycarbonate layer with a thickness of 10 μm. Then, the elongation at break test was performed according to GB / T 30776-2014 "Test method for tensile strength and elongation at break of adhesive tapes". The test results are as follows:

[0076] From the data in the above table, it can be concluded that the peel strength and elongation at break of the OCA optical adhesive prepared in Examples 1 to 3 of the present invention are relatively high, and the peel strength value after high-temperature treatment changes slightly, indicating that the peel strength, high-temperature resistance and flexibility are excellent; the peel strength of the OCA optical adhesive prepared in Comparative Example 1 is excellent, and compared with the embodiment, the elongation at break is relatively low, and the peel strength value after high-temperature treatment changes significantly, so the high-temperature resistance and flexibility are poor, which is presumably due to the fact that no inorganic modified additives are added during the preparation of the OCA optical adhesive; the flexibility of the OCA optical adhesive prepared in Comparative Example 2 is excellent, the peel strength value after high-temperature treatment changes slightly, and the high-temperature resistance is good. Compared with the example, the peel strength value is lower, which is speculated to be due to the fact that no rosin composite resin cross-linking agent is added during the preparation of the OCA optical adhesive; the OCA optical adhesive prepared in Comparative Example 3 has excellent peel strength performance, and has a lower elongation at break value than the example, and the peel strength value changes greatly after high-temperature treatment. It is speculated that this is due to the agglomeration of talc powder during the preparation of the OCA optical adhesive, resulting in poor high temperature resistance and flexibility of the OCA optical adhesive compared to the OCA optical adhesive prepared in the example; the peel strength and elongation at break values ​​of the OCA optical adhesive prepared in Comparative Example 4 are both lower, and the peel strength value changes greatly after high-temperature treatment, indicating that its peel strength, high temperature resistance and flexibility performance are poor.

[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process of acrylic ester OCA optical adhesive for folding screens, characterized in that: The following steps are involved: (1) In parts by weight, under the protection of nitrogen, add 30-70 parts of butyl methacrylate, 3-5 parts of acrylic acid, 20-50 parts of glycidyl acrylate, 0.6-5 parts of initiator and 0.4-1 parts of rosin composite resin crosslinking agent into a reactor, raise the temperature to 50-70°C, stir for 1-2 hours, then add 2-4 parts of inorganic modified additives, continue stirring for 1-3 hours, and obtain an adhesive; (2) placing the adhesive in a vacuum drying oven at a temperature of 60 to 70° C. for curing for 5 to 10 minutes to form a glue compound, and then pressing the glue compound into a sheet-like film, cooling it, and then packaging it with a release film to obtain an acrylate OCA optical adhesive; The initiator is any one of dicumyl peroxide and benzoyl peroxide; The production process of the rosin composite resin cross-linking agent comprises the following steps: S1: under the protection of nitrogen, epoxy compound, chloroacetic acid resin and rosin resin are added to toluene, and then a catalyst is added, and refluxed and stirred for 2 to 4 hours. After the reaction is completed, the product is filtered, and then washed and dried to obtain a modified rosin composite resin; S2: adding the modified rosin composite resin and acryloyl chloride into toluene, stirring until completely dissolved, then adding pyridine, mixing evenly, reacting at 30-40° C. for 4-10 hours, and after the reaction, performing reduced pressure distillation and vacuum drying on the product to obtain a rosin composite resin crosslinking agent; The epoxy compound is any one of ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and 1,4-butanediol diglycidyl ether; The catalyst is any one of tetrabutylammonium bromide and tetramethylammonium bromide; The production process of the inorganic modified additive comprises the following steps: Ⅰ: Add 2,3-epoxypropyltrimethylammonium chloride, talc and deionized water into the reactor, stir to mix them evenly, then start to drop sodium hydroxide solution, adjust the pH value of the system to keep it between 9.5 and 10, place it at 70 to 90° C. for aging for 5 to 10 hours after the dropwise addition, then centrifuge and wash to obtain intercalated modified talc; Ⅱ: Mix the polyetheramine and isopropanol, raise the temperature to 60-80°C, stir evenly, then add the intercalation modified talc, react for 10-20 hours, cool the product to room temperature after the reaction, filter and separate the solid sample, wash and vacuum dry to obtain the inorganic modified additive; The particle size of the talc is 15 to 25 μm; The mass ratio of the intercalated modified talc powder to the polyetheramine is 1:1-2; The number average molecular weight of the polyetheramine is 1000.

2. An acrylic ester OCA optical adhesive for folding screen, characterized in that: The method is manufactured by the production process as claimed in claim 1.

Citation Information

Patent Citations

  • An OCA optical adhesive and an OCA optical adhesive film

    CN107353854B

  • Preparation method of flexible, highly-waterproof and high-temperature-resistant OCA optical adhesive and OCA optical adhesive film

    CN116790221A

  • OCA (Optical Clear Adhesive) for flexible folding screen and preparation method of OCA

    CN115710477A

  • OCA (Optical Clear Adhesive) for folding screen as well as preparation method and application of OCA

    CN115895523A